Chapter Black Sea and its Maritime Networks, 1770s-1820s. The Beginnings of Its European Integratio - Harlaftis, Gelina (Atti delle «Settimane di Studi» e altri Convegni, 2019)
This paper examines the first 50 transitional years of a sea of isolation to a sea of internationalization. It provides analytical tools to reveal the mechanisms of how this was done. To do so it places in the centre of the analysis the sea. By using the approach of maritime history, an analysis beyond political borders, it follows the glance from the sea and its effects on land. In this way it examines the shipping movements of cargoes and people on the sea and the development and impact of this developmentaround the sea, on the Black Sea maritime regions, the port cities that grew and the entrepreneurs that triggered this growth and established its maritime networks.